Comparative study of hybrid and wild black poplar genotypes in the first three-year cycle of multi-stem short-rotation coppice. (March 2019) - Saulino, Luigi; Allevato, Emilia; Todaro, Luigi; Rossi, Sergio; Bonanomi, Giuliano; Saracino, Antonio
Abstract: In short-rotation coppice, shoots grow at high density and compete for limiting resources with their neighbours. Interactions among shoots translate into individual size differences due to resource apportionment. In the present study we compared shoot dynamics of six hybrid poplars and three wild river genotypes of Populus nigra under the first three-year cycle of multi-stem short-rotation coppice. We investigated changes over time in diameter frequency distribution, mortality and biomass partitioning according to crown classes of the shoots. Unimodal shoot diameter distributions during rotation modelled by a two-parameter Weibull probability density distribution show that the values of the α scale parameter are higher in hybrid genotypes compared to wild black poplars ( α  ≥ 2.0 and α  ≤ 2.0, respectively) in all three years. The values of the β shape parameter mostly decrease over time in hybrid genotypes and increase in wild black poplars in the narrow range from 1.42 to 2.38 and from 1.47 to 2.03, respectively. With regard to biomass partitioning among shoot crown classes, differences in size attributes are more pronounced in hybrids than native black poplar genotypes. In hybrid genotypes, 83.7% of the biomass is allocated to dominant shoots, while wild black poplars share 71.6% of the biomass in the dominant and 24.8% in the intermediate shoots. This disproportional biomass allocation among crown classes of hybrid compared to native genotypes could be related to their different origin of selection. Highlights: Two-parms Weibull PDF depicts shoot diameter distribution over time of poplars in SRC. Weibull PDF diameter distributions change over time due to population dynamic. Different biomass partitioning characterizes native wild and domesticated poplars. Differences in size attributes are more pronounced in hybrids than native black poplar genotypes.